Service modularity and architecture – an overview and research agenda - Brax, Saara A; Bask, Anu; Hsuan, Juliana; Voss, Chris (International journal of operations & production management, 2017)
Purpose Services are highly important in a world economy which has increasingly become service driven. There is a growing need to better understand the possibilities for, and requirements of, designing modular service architectures. The purpose of this paper is to elaborate on the roots of the emerging research stream on service modularity, provide a concise overview of existing work on the subject, and outline an agenda for future research on service modularity and architecture. The articles in the special issue offer four diverse sets of research on service modularity and architecture. Design/methodology/approach The paper is built on a literature review mapping the current body of literature on the topic and developing future research directions in service modularity and architecture. Findings The growing focus on services has triggered needs to investigate the suitability and implementation of physical-product-focused modularity principles and theories in service contexts, and to search for principles/theories that enhance services. The expanding research stream has explored various aspects of service modularity in empirical contexts. Future research should focus on service-specific modularity theories and principles, platform-based and mass-customized service business models, comparative research designs, customer perspectives and service experience, performance in context of modular services, empirical evidence of benefits and challenges, architectural innovation in services, modularization in multi-provider contexts, and modularity in hybrid offerings combining service and tangible product modules. Originality/value Nine areas are recommended for further research on service modularity and architecture. The introductory piece also discusses the roots of service modularity and provides an overview of current contributions.